Pengaruh Pelatihan Kerja dan Pengembangan Karir Terhadap Kinerja Pegawai Non medis Pada Rumah Sakit Umum Daerah Sekayu - Dewi Puspita Rahayu; Fauziah Afriyani; Meilin Veronica (Universitas Islam Kadiri, 2023)
This research was conducted at Sekayu Regional General Hospital. This study uses a type of quantitative research. The method used in this study was a saturated sample of 70 non-medical employee respondents and used data analysis in the form of data instrument testing, classical assumption testing, multiple linear regression testing, hypothesis testing. The purpose of this study was to find out (1) How does job training affect the performance of non-medical employees at Sekayu General Hospital. (2) How does the influence of career development on the performance of non-medical employees of Sekayu General Hospital. (3) What is the effect of job training and career development on the performance of non-medical employees at Sekayu Hospital. The results of the t-test data processing show that job training has a positive and significant effect on employee performance with a sig. 0.039 <0.05 and from tcount > ttable or (2.107 > 1.667). Career development has a positive and significant effect on employee performance with a sig. 0.036 <0.05 and from tcount > ttable or (2.145 > 1.667). Based on the F test, job training and career development have a positive and significant effect with a sig. 0.002 <0.05 and from Fcount > Ftable or (6.941 > 3.130). Based on the results of the multiple linear regression test, the equation is Y = 9.007 + 0.175 X1 + 0.207 X2 + 2.427.